2015
DOI: 10.1063/1.4928867
|View full text |Cite
|
Sign up to set email alerts
|

Properties of aqueous nitrate and nitrite from x-ray absorption spectroscopy

Abstract: Nitrate and nitrite ions are of considerable interest, both for their widespread use in commercial and research contexts and because of their central role in the global nitrogen cycle. The chemistry of atmospheric aerosols, wherein nitrate is abundant, has been found to depend on the interfacial behavior of ionic species. The interfacial behavior of ions is determined largely by their hydration properties; consequently, the study of the hydration and interfacial behavior of nitrate and nitrite comprises a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 49 publications
(54 reference statements)
7
23
1
Order By: Relevance
“…The main edge shape itself is split in two peaks, one at 538 eV and the other at 543 eV, that can be attributed to the strong influence of hydrated and/or hydrolysed forms of Pu(IV) on the total oxygen state3132. In addition, the contribution from nitrate ions to the experimental O K-edge NEXAFS spectra of hydrolytic Pu colloid also cannot be completely excluded33. It can be concluded that the difference between the two studied colloids is the stronger influence of hydrolysed Pu(IV) moieties at the surface shell of the smaller colloidal nanoparticles (hydrolytic).…”
Section: Resultsmentioning
confidence: 99%
“…The main edge shape itself is split in two peaks, one at 538 eV and the other at 543 eV, that can be attributed to the strong influence of hydrated and/or hydrolysed forms of Pu(IV) on the total oxygen state3132. In addition, the contribution from nitrate ions to the experimental O K-edge NEXAFS spectra of hydrolytic Pu colloid also cannot be completely excluded33. It can be concluded that the difference between the two studied colloids is the stronger influence of hydrolysed Pu(IV) moieties at the surface shell of the smaller colloidal nanoparticles (hydrolytic).…”
Section: Resultsmentioning
confidence: 99%
“…The polyoxy‐anions form a major class of ions which have great relevance to various atmospheric and biological systems. These ions have multiple charge centers and their effects on the structure and dynamics of water have been the topic of many earlier studies in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Unoccupied electronic states can be accessed using other techniques, such as near-edge x-ray absorption fine structure spectroscopy (NEXAFS), which probes the excitation of atomic core electrons to unoccupied molecular orbitals. Because these orbitals are sensitive to the local chemical environment, NEXAFS is more sensitive to the structure and bonding of solutions than x-ray PE spectroscopy, and it has been used to determine the solvation environments of several of the molecules studied here, such as CO 3 2− , HCO 3 − , and NO 3 − ( 28 , 29 ). …”
Section: Introductionmentioning
confidence: 99%